Assesment of studing learning 1 - Buendicho, Flordeliza C. (Manila, 2010)
Assessment of student learning 1 is a three-unit professional education course. It is one of the theory and concept courses. It provides the broad framework within which the methods, strategies, processes, issues, and other matters related to teaching are included and discussed
Keywords: Educational tests and measuremetns; Learning